(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Myricetin is considered a flavonols under the category of flavonoids. According to recent research, myricetin has different curative effects on diabetes, cancer, and the heart. It has been suggested that myricetin is a more potent antioxidant than quercetin. The present study aimed to investigate the wound healing effect of myricetin loaded nanoemulsion (MYCT-NE) gel formulation in diabetic animals. Myricetin-loaded nanoemulsion was converted in nanoemulsion gel using carbopol 934 and evaluated for diabetic wound healing effect against wound contraction measurement, hydroxyproline estimation, protein estimation, antioxidant assay and histopathological study. On day 18th of treatment, the wound contraction of Faster wound healing was observed in the MYCT-NE gel treated groups compared to the control group, as indicated by a shorter epithelialization duration. Increased collagen turnover was shown by increased hydroxyproline levels in MYCT-NE gel-treated tissue, which sped up the healing of treated wounds. MYCT-NE gel possesses effective antioxidant activity by restoration of the superoxide dismutase SOD, GSH and catalase level in the wound tissues after treatment and healing. The observations showed that the original tissue regeneration was found efficiently in the wound treated with MYCT-NE gel and reference group without edema and congestion. The results obtained in the present study were indicated that MYCT-NE gel accelerates cutaneous diabetic wound healing through reducing oxidative status in experimental animals.